Pollen morphology of twenty three species of Allium L. (Amaryllidaceae) species from Turkey - Yildiz , Ümmügülsün (Bangladesh Journal of Plant Taxonomy, 2023)
The pollen morphology of 23 Allium L. species, grown in Turkey, belonging to the sections; Rhizirideum, Schoenoprasum, Cepa, Molium, Brevispatha, Scorodon, Acanthoprason and Melanocrommyum, were investigated by LM (light microscopy), TEM (transmission electron microscope), and SEM (scanning electron microscopy). This paper presents detailed pollen morphological features are given for these taxa. Common characteristics of pollen of Allium species investigated are ellipsoidal and heteropolar, bilateral symmetry; pollen grains are shed as monads. They are monosulcate (extended sulcate types) and monosulcate-operculate. The sculpturing of the exine, pollen membrane ornamentation, lumina shape, and sulcus membrane with a fragmented operculum are found to be characteristic features for separating species. Based on these properties three main pollen types were determined with three different exine sculpturing. The characteristic structures of pollen ornamentation, observed in SEM micrographs, are striateperforate, striateregulate-perforate and regulate-perforate. Sulcus membrane ornamentations are psilate, psilate-perforate, rugulate and regulate-perforate. The exine is semitectate and the tectum perforate. Columellae were found to be simplicolumellate. Bangladesh J. Plant Taxon. 30(1): 1-19, 2023 (June)